Transoperative Hemodynamic Status and Delayed Graft Function: Analysis of 42 Consecutive Renal Transplantation - Pimpao, Bruno de Figueiredo (2023)
Objective: Evaluate the correlation between transoperative hemodynamic status and development of delayed graft function (DGF) in patients undergoing kidney transplantation. Methods: We analyzed 42 consecutive renal transplants between May 2021 and May 2022 in a University Hospital. Four kinds of variables were assessed. Recipients variables: age, gender, race, type of dialysis, dialysis time before transplantation and residual diuresis. Donor variables: age, serum creatinine level, death cause, race, laterality of the kidney (right or left kidney), perfusion solution and Kidney Donor Profile Index (KDPI). Surgical variables: cold Ischemia time (CIT), vascular multiplicity, the surgeon, duration of surgery and blood pressure during the procedure. Immunological variables: Panel reactive antibodies (PRA), HLA mismatches and the need of induction therapy with antithymocyte globulin. Results: In univariate analysis, regarding recipients’ factors, type of dialysis (hemodyalisis) (p=0.004) and absence of residual diuresis (p=0.011) were significant on the development of DGF.  Among the donors, only the laterality of the kidney (rightkidney) was statiscally significant (p=0.005). The cold ischemia time higher than 24 hours (p=0.022), systolic blood pressure (SBP) less than 130 mmHg at reperfusion (p<0.001), Mean Arterial Pressure (MAP) less than 80 mmHg at the reperfusion (p<0.001), and mean MAP post-reperfusion (p=0.049) were the significant surgical factors for DGF. Among immunological factors, the patients that received antithymocyte globulin as induction therapy more frequentlydeveloped DGF (p=0.036). Only MAP < 80 mmHg (p=0.004) and SBP < 130m mmHg (p=0.005) were independent risk factors for DGF. Conclusion: In this survey, optimal renal perfusion, avoiding fall in blood pressure in the transoperative period, especially after graft reperfusion, is crucial for the immediate functioning of the kidney.